Prinsip-Prinsip Etika dari "tinggal di dalam" dari perspektif Yohanes - Nainggolan, Cathryne Berliana (Diligentia: Journal of Theology and Christian Education, 2025)
Johannine Literature is known for its rich theological perspective. Grounding from his theological standpoints, he draws his ethical principles. One of the disputes in this book is whether John has explicit or implicit ethical implications for his teaching. The methodology used in this paper is a literature review using exegetical sources. This paper focuses on one of John’s teachings, “abiding in” and its ethical principles.  The concept of “abiding in” portrays the identity and authority of Jesus related to His Father, the status and fellowship between Jesus and His disciples, as a mark of true or false disciples, and as a basis to live as Jesus lived. Deriving from this concept, abiding in Jesus is the ground of ethical principles: living in the light, loving others, and obeying the truth.